Antenatal care coverage of pregnant mothers in Tamil Nadu: evidence from National Family Health Survey 4 - Raju, Mohankumar (International Journal Of Community Medicine And Public Health, 2020)
Background: The sustainable development goal emphasises on reduction in mothers dying due to pregnancy. Recommended care for the pregnant mothers will help achieve this goal. Tamil Nadu is one of the best performing state in maternal and child health care. Author analysed the full antenatal care coverage of pregnant mothers of the districts of Tamil Nadu by using National Family Health Survey (NFHS)-4 data. Methods: Author did a secondary data analysis of NFHS 4 data for the districts of Tamil Nadu for understanding the MCH coverage. Results: Tamil Nadu showed 45% full AN coverage with 46.3% in urban and 43.8% in rural population, among 32 districts, Krishnagiri (65.5%) is the best performing and Virudhunagar (13.7%) is the poorest performing district of Tamil Nadu. Full AN coverage includes at least 4 AN check-up, vaccination of tetanus toxoid and consumption of 100 IFA tablets in last pregnancy. Tamil Nadu showed 81.1% of at-least 4 AN visit, 71% with vaccination for TT and 64% on consumption of 100 IFA tables. Similar coverage trend among the components of full ANC coverage is seen among all the districts of Tamil Nadu. Conclusion: Focusing on the coverage of IFA tablet consumption and also showing special interest among the rural population will increase the coverage. A detailed assessment for understanding the reasons for poor performance among the districts of Tamil Nadu is needed for better evidence-based practices.